Pengaruh Gaya Hidup Halal, Label Halal Dan Harga Terhadap Keputusan Pembelian Ms Glow (Studi Pada Mahasiswi Universitas Trunojoyo Madura) - Yuliana Ulfidatul Hoiriyah; Yustina Chrismardani (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This study aims to see the effect of the halal lifestyle, the halal label, and the price of MS Glow’s product on the purchase decision of students of Trunojoyo Madura University from 2017 to 2020. Sampling in this study used accidental sampling with a total of 100 respondent, and analyzed using multiple linear regressions analysis. Based on the partial analysis, the result show, that each variables (halal lifestlye, halal label and price) has a significant effect on the purchase decision of MS Glow of the students of Trunojoyo Madura University.